2015
DOI: 10.17221/530/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of digestate, cattle slurry and mineral fertilization on the winter wheat yield and soil quality parameters

Abstract: This study compares the effect of application of digestate, straw, cattle slurry and inorganic fertilizers on crop yield and soil organic matter content. Total organic carbon (C), total organic nitrogen (N), hot water soluble C, microbial biomass C and hydrophobic soil components were evaluated in soil from the field experiment in PragueRuzyně (Orthic Luvisol, clay loam) with winter wheat. All fertilized treatments significantly increased grain yield above the level of non-fertilized control (5.68 t/ha), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…Similar results have been reported in several studies where they showed digestate affected wheat growth and yield differently compared with raw manure (Abubaker et al, 2012;Adelekan et al, 2010;Šimon et al, 2015). The application of DCM and DPM with and without combination with urea increased crop biomass yield in comparison with application of sole manure.…”
Section: Root Straw Ears and Total Biomasssupporting
confidence: 86%
“…Similar results have been reported in several studies where they showed digestate affected wheat growth and yield differently compared with raw manure (Abubaker et al, 2012;Adelekan et al, 2010;Šimon et al, 2015). The application of DCM and DPM with and without combination with urea increased crop biomass yield in comparison with application of sole manure.…”
Section: Root Straw Ears and Total Biomasssupporting
confidence: 86%
“…Table reports the soil TKN values detected during incubation for the different treatments. The TKN content was subject to minimal variation caused by ammonia volatilization or denitrification processes ( Šimon et al, ). More interesting was the evolution of the different chemical forms of nitrogen, in particular N‐NH 4 and N‐NO 3 during incubation (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…In a comparative assessment of digestate, cattle manure, and mineral fertilization for winter wheat, Simon et al . reported significant increase in grain yield with the trend as follows; digestate > chemical fertilizer > cattle manure > control. However, digestate with high biodegradable fraction may not be suitable for agricultural use as they might lead to N‐immobilization .…”
Section: Introductionmentioning
confidence: 97%
“…In relation to its undigested counterpart, digestate application is found to be better in terms of crop yield mainly because of improved N nutrition of the crops [18,19]. In a comparative assessment of digestate, cattle manure, and mineral fertilization for winter wheat, Simon et al [20] reported significant increase in grain yield with the trend as follows; digestate > chemical fertilizer > cattle manure > control. However, digestate with high biodegradable fraction may not be suitable for agricultural use as they might lead to N-immobilization [21,22].…”
Section: Introductionmentioning
confidence: 99%